(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This research investigates the application of Delta-Sigma Modulator controlled switch-mode power supplies to address the challenges associated with conventional PWM-controlled DC-DC Buck Converters. By exploiting the noise-shaping capabilities of Delta-Sigma modulation, in-band tones in the output are mitigated. The study encompasses three phases: initial design and performance evaluation of PWM-controlled converters, transition to Delta-Sigma Modulator control, and refinement of the design to enhance efficiency and noise performance. Notable achievements include reducing inductor values and integrating on-chip capacitors, leading to a peak efficiency of 91% at a 200MHz sampling frequency. Post-layout simulations further validate the superiority of Delta-Sigma Modulator controlled switch-mode power supplies over PWM-controlled counterparts.